Analysis of the molecular mechanism endogenous hormone regulating axillary bud development in Pinus yunnanensis - Haihao He; Junfei Xu; Nianhui Cai; Yulan Xu (BMC Plant Biology)
Abstract Background P. yunnanensis, a distinctive economic tree species native to Yunnan Province in China, possesses axillary buds that serve as superior material for asexual propagation. However, under natural growth conditions, the differentiation of these axillary buds is notably scarce. In this study, we employed decapitation to stimulate the development of axillary buds in P. yunnanensis. Subsequently, we assessed the phytohormone levels in both axillary and apical buds, and conducted a comprehensive transcriptomic analysis complemented by RT-qPCR validation. Results We found that decapitation could effectively promote the releases of the axillary buds in P. yunnanensis. The levels of cytokinin, auxin, gibberellin and abscisic acid in axillary buds were higher than those in apical buds, and the difference in gibberellin levels was the greatest. The transcriptome sequencing results were highly reproducible, and the relative expression levels of the 13 genes screened were highly consistent with the FPKM value trend of transcriptome sequencing. There were 2877 differentially expressed genes (DEGs) between axillary buds and terminal buds, and 18 candidate genes (CGs) involved in axillary bud release were screened out. A total of 1171 DEGs were identified during the analysis of axillary bud growth, and 14 CGs involved in axillary bud growth and development were screened out. GO and KEGG enrichment analysis were performed on the DEGs. Furthermore, combined with the results and discussion, the functions of the candidate genes were analyzed and a possible regulatory network was constructed. Conclusion The findings and discussions indicated that the development of axillary buds in P. yunnanensis is predominantly governed by cytokinin, gibberellin, strigolactone, and auxin, as well as their biosynthesis and regulatory genes, which are crucial to the development of these buds. This study has, to some extent, bridged the research gap concerning the development of axillary buds in P. yunnanensis and has provided foundational data to support further research into the developmental mechanisms of these buds and the establishment of asexual propagation cutting nurseries.